Chondral Disease of the Knee A Case-Based Approach - Cole, Brian J.; Malek, M. Mike.; SpringerLink (Online service) (New York, NY : Springer New York, 2006)
This valuable resource, derived from Drs. Cole and Malek$1 (Bs Articular Cartilage Lesions: A Practical Guide to Assessment and Treatment, features case studies that help the reader develop an understanding of chondral disease and hone the decision-making skills integral to successful cartilage repair and solution implementation. The case studies included were selected for optimum clinical value and cover such issues as injury evaluation, physical examination, radiographic evaluation, and comorbidities. Each case is complemented by brilliant illustrations, many in color, and concludes with bulleted decision-making factors that can be easily incorporated into clinical practice. This practical, case-based book is an ideal learning tool for residents and surgeons seeking to gain a better understanding of chondral disease and the many approaches to its successful treatment.s
Osteochondritis dissecans of the medial femoral condyle with documented long-term natural history -- Avascular necrosis -- Unstable in situ osteochondritis dissecans of the medial femoral condyle -- Unstable in situ osteochondritis dissecans of the medial femoral condyle -- Concomitant medial meniscus tear and focal chondral defect of the medial femoral condyle -- Isolated focal chondral defect of the medial femoral condyle -- Symptomatic focal chondral defect of lateral femoral condyle -- Isolated small grade IV medial femoral condyle chondral lesion -- Isolated medial compartment osteoarthritis -- Unicompartmental bipolar disease -- Medial femoral condyle focal chondral defect -- Lateral femoral condyle focal chondral defect -- Focal chondral defect of the medial femoral condyle and patella -- Lateral femoral condyle osteochondritis dissecans -- Focal chondral defect of the lateral femoral condyle -- Contained focal chondral defect of the medial femoral condyle -- Contained focal chondral defect of the medial femoral condyle -- Osteochondritis dissecans of the medial femoral condyle -- Osteochondritis dissecans of the lateral femoral condyle -- Uncontained focal chondral defect of the lateral trochlea -- Failed prior fresh osteochondral allograft of the medial femoral condyle -- Lateral meniscus deficiency -- Prior medial meniscectomy and focal chondral defect medial femoral condyle -- Failed anterior cruciate ligament reconstruction with medial meniscus deficiency -- Advanced patellofemoral arthritis -- Multiple chondral defects -- Traumatic patellar instability with focal chondral defect of the patella -- Focal chondral defect patella -- Focal chondral defect medial femoral condyle and varus alignment -- ACL deficiency with symptomatic trochlear and medial femoral condyle chondral lesions -- Focal chondral defect of the medial femoral condyle in a previously meniscectomized knee -- Focal chondral defect lateral femoral condyle, prior lateral meniscectomy, and small focal chondral defect lateral tibial plateau -- Bipolar focal chondral defects of the patellofemoral joint with patellar instability -- Bipolar focal chondral defects of the patellofemoral joint -- Lateral compartment tibiofemoral degenerative arthrosis -- Isolated patellofemoral arthritis -- Posttraumatic medial femoral condyle defect, varus instability, and deformity with significant motion loss -- Chondral defects with prior medial and lateral meniscectomy and varus alignment.
Keywords: Medicine; Orthopedics; Sports medicine; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Sports Medicine; Electronic books